011 Clinical Experience with Testosterone Undecanoate Capsules (Jatenzo): The First 50 Patients. (1st May 2022) - Yee, A.; Uloko, M.; Goldstein, I.
ABSTRACT: Introduction: Testosterone Undecanoate (TU) Capsules (Jatenzo, Clarus Therapeutics) was FDA-approved as a testosterone replacement therapy (TRT) for adult males with primary or secondary hypogonadism in 2019. We have now over 100 patients using TU capsules. The capsule is an oral self-emulsifying drug delivery system that is a highly lipophilic prodrug carried with lipoproteins into intestinal lymphatics, thus avoiding first pass metabolism of testosterone by the liver. Entrance into the left subclavian vein at the thoracic duct allows esterases to release active testosterone from the TU prodrug. Objective: To review our experience with TU capsules in our first 50 patients, including initial patient experiences, medication drop-out rate, and relevant side effects. Methods: This is a retrospective chart review of our patients prescribed and using TU capsules. We follow the PI regarding titration to identify the ideal TU capsule dose. Instructions to the patient included taking the capsule with some fat (spoonful of peanut butter, almond butter, or avocado). Based on TU reaching steady state at only 7 days, patients were instructed to take the 237 mg tablet in the morning and at lunchtime get a testosterone blood test. If the dose was adjusted, the patient repeated the above protocol at 7 days post dose adjustment. Results: The study group consisted of the first 50 patients at our facility (mean age 54 +/- 9 years) who were prescribed and received the TU capsules. 82% of patients were on TRT previously; 49% had been on IM testosterone cypionate; 27% on testosterone gels. The mean testosterone value for these patients prior to TU capsule use was 347 +/- 86 ng/dl. This was higher than the clinical trial data as we did not require discontinuation of other TRT prior to starting treatment with TU capsules. Overall, 61% of patients remained at 237 mg BID TU capsules, 26% were titrated to 158 mg tabs x 2 BID, and 12% were titrated to 198 mg tabs x 2 BID. One patient's starting dose was reduced to 198 mg BID as his testosterone was elevated at the starting dose. Patients using other TRT's prior to TU capsules reported enjoying no longer needing IM injection, pellet insertion, negative aspects of gel such as messiness or transference to others. For patients for whom we had a baseline SHBG value, SHBG lowered in all patients with TU capsule use, thus increasing free testosterone values. For patients for whom we had a baseline dihydrotestosterone value, dihydrotestosterone increased in all patients, providing higher values than with other TRT strategies. No increase in hematocrit requiring phlebotomy was observed, nor hypertension requiring treatment. One patient discontinued TU capsule use due to bothersome heartburn. The large capsule size (2.5 cm long and 1 cm wide) was not a reason for discontinuation as the smooth capsule is easy to swallow. There were no liver function test abnormalities. Some patients observed increased erection function/libido several hours after taking TU capsules. Conclusion: Our initial experience with TU capsules for the treatment of hypogonadism has been very favorable. Disclosure: Work supported by industry: no.